(Invited) Molecular Layer Deposition from Dissolved Precursors. (14th August 2017) - Fichtner, Johannes; Wu, Yanlin; Hitzenberger, Jakob; Drewello, Thomas; Bachmann, Julien
Abstract : We present a procedure for growing thin films of an organic polyamid material based on a cyclic repetition of two consecutive, complementary, self-limiting surface reactions. The molecular compounds that react with the surface are dissolved in an organic solvent. This new method exemplifies how atomic layer deposition (ALD) and molecular layer deposition (MLD) can benefit from being transferred from the gas phase to the liquid phase, given that a broad variety of advantageous reagents are only available in dissolved form.